COINTEGRATION ANALYSIS OF CRYPTOCURRENCY MARKET - TROIAN, Kyrylo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study investigates the internal dynamics of the cryptocurrency market through a comprehensive analysis of cointegration relationships and their association with trading volumes. By examining 71,687 cryptocurrency pairs, we find that 79.06% demonstrate significant cointegration at the 95% confidence level, indicating substantial market integration within the cryptocurrency ecosystem. The analysis reveals distinct patterns of integration across different cryptocurrency categories, with NFT/Gaming, metaverse, and interoperability tokens showing particularly high levels of cointegration (>90%), while stablecoins and storage tokens exhibit relatively lower levels (<80%). The strongest cointegration relationship was observed between platform tokens and leverage tokens, with a test statistic of 704.20. The research identifies a complex and nuanced relationship between trading volume and market integration. A weak negative correlation (ρ = -0.0560) between cointegration test statistics and average trading volumes was found to be statistically significant (p = 4.2665e-56), challenging conventional assumptions about the role of trading activity in market integration. Analysis of volume quantiles revealed relatively stable cointegration patterns across most trading volumes, with a notable peak in the highest quantile, suggesting non-linear relationships in high-volume market segments. Our findings contribute to the understanding of cryptocurrency market structure and have significant implications for portfolio management, risk assessment, and market regulation. The high degree of market integration suggests increased systematic risk and the need for sophisticated diversification strategies. The category-specific variations in cointegration patterns provide insights for portfolio construction and risk management. These results enhance our understanding of cryptocurrency market dynamics and offer valuable insights for market participants, researchers, and regulators in navigating the evolving digital asset ecosystem.